Common and Specific Functional Activity Features in Schizophrenia, Major Depressive Disorder, and Bipolar Disorder - Yang, Yongfeng; Liu, Shu; Jiang, Xiaoyan; Yu, Hongyan; Ding, Shuang; Lu, Yanli; Li, Wenqiang; Zhang, Hongxing; Liu, Bing; Cui, Yue; Fan, Lingzhong; Jiang, Tianzi; et al. (Frontiers in Psychiatry, 2019)
Objectives: Schizophrenia (SZ), major depressive disorder (MDD) and bipolar disorder (BD) are serious mental disorders with distinct diagnostic criteria. They share common clinical and biological features. However, there are still only few studies on the common and specific brain imaging changes associated with the three mental disorders. Therefore, the aim of this study to was to identify the common and specific functional activity and connectivity changes in SZ, MDD, and BD. Methods: A total of 271 individuals underwent functional magnetic resonance imaging: SZ (n = 64), MDD (n = 73), BD (n = 41), and healthy controls (n = 93). The symptoms of SZ patients were evaluated by the Positive and Negative Syndrome Scale. The Beck Depression Inventory (BDI), and Beck Anxiety Inventory (BAI) were used to evaluate the symptoms of MDD patients. The BDI, BAI, and Young Mania Rating Scale were used to evaluate the symptoms of MDD and BD patients. In addition, we compared the fALFF and functional connectivity between the three mental disorders and healthy controls using two sample t-tests. Results: Significantly decreased functional activity was found in the right superior frontal gyrus, middle cingulate gyrus, left middle frontal gyrus, and decreased functional connectivity of the insula was found in SZ, MDD, and BD. Specific fALFF changes, mainly in the ventral lateral prefrontal cortex, striatum, and thalamus were found for SZ, in the left motor cortex and parietal lobe for MDD, and the dorsal lateral prefrontal cortex, orbitofrontal cortex, and posterior cingulate cortex in BD. Conclusion: Our findings of common abnormalities in SZ, MDD, and BD provide evidence that salience network abnormality may play a critical role in the pathogenesis of these three mental disorders. Meanwhile, our findings also indicate that specific alterations in SZ, MDD, and BD provide neuroimaging evidence for the differential diagnosis of the three mental disorders.